Peran Guru Pendidikan Agama Islam dalam Menanamkan Nilai-Nilai Kejujuran pada Siswa di SMP Negeri 5 Sangatta Utara - Ahmad Anshari; Faelasup Faelasup; Mukhtar Mukhtar (STIKes Ibnu Sina Ajibarang, 2025)
The purpose of this study is to identify the forms of honesty values, the role of Islamic Religious Education teachers, as well as obstacles and solutions in instilling honesty values ​​in students of SMP Negeri 5 Sangatta Utara. The phenomenon of dishonesty in the school environment shows a gap between religious understanding and students' moral practices. Using a qualitative research type with a phenomenological approach, data was collected through interviews, observations, and documentation, then analyzed using the Miles and Huberman techniques, namely data condensation, data presentation, verification/conclusion. The results of the study showed three forms of honesty values: not playing truant, doing assignments well, and an honesty canteen program. Islamic Religious Education teachers act as role models, motivators, and integrate honesty values ​​into extracurricular activities (Rebana/Habsyi). The obstacles faced include student boredom, lack of approach, and the influence of the environment and parents who are less supportive. The solutions implemented by Islamic Religious Education teachers are to provide motivation, be role models, build close relationships with students and parents, and utilize religious values ​​through extracurricular activities such as Rebana/Habsyi.